A central region upgrade of the k800 Superconducting Cyclotron at INFN-LNS. (November 2019) - D'Agostino, G; Calabretta, L; Kleeven, W; Rifuggiato, D
Abstract: The Superconducting Cyclotron (CS) at INFN-LNS in Catania is currently under an upgrade process. The plan is to deliver beams of ions with mass number A ⩽ 40 with power up to 10 kW by means of beam intensity increase. This ambitious goal can be achieved by increasing the efficiency of the injection and extraction processes. An extraction efficiency close to 100% is expected by extracting the specific ion beams from the CS by stripping and no longer by electrostatic deflectors. The beams are injected axially and bent onto the median plane with a spiral inflector. Currently, the injection efficiency is around 15% including the effect of a drift buncher placed in the axial injection line. In order to increase the injection efficiency, the study of an upgraded CS central region is ongoing at INFN-LNS. In this paper, the results of simulations of beam tracking through the cyclotron axial bore, the spiral inflector, the central region and further up to the extraction system are presented.